Wisada Sawah: Sumber Pengetahuan Pengelolaan Sawah dalam Tradisi Masyarakat Bali - Wijaya, Made Paramasuta; Cika, I Wayan; Suardiana, I Wayan (Humanis; Vol 26 No 2 (2022)DO - 10.24843/JH.2022.v26.i02.p01, 2022)
This study aims to provide knowledge in the field of agriculture that comes from traditional texts to the community. This study discusses the problems of (1) the form of rice field management in the Wisada Sawah text; (2) function; and (3) the meaning of the Wisada Sawah text. Data were collected using the library method, then analyzed using descriptive-analytical methods, and presented using informal methods. The theory used in this study are the theory of discourse, function, and semiotics. This study succeeded in revealing the form of rice field management on a s?kala and niskala. The analysis of the function and meaning of the Wisada Sawah text is related to the dimensions of cognition and social context, that is the context of a society with agrarian culture. The functions of the Wisada Sawah text are religious functions, ecological functions, and social functions. The meaning of the Wisada Sawah text is the harmonious relationship between humans and God, the harmonious relationship between humans and nature, and the harmonious relationship between human beings.